Generation of diffraction-free beam with winding trajectory based on metasurface holography - Jilian Xu; Peiyao Lu; Rui Wu; Kun Jiang; Xiquan Jiang; Shuyun Teng (New Journal of Physics, 2024)
The diffraction-free beams with curved trajectories and shaped wavefronts have wide application prospects in many fields. This paper proposes the generation of diffraction-free beam with winding trajectory and spiral wavefront based on holographic metasurface. The holographic metasurface consists of rotated rectangular nanoholes and the winding trajectory for the generated diffraction-free beam may be in two or three dimensional space under the control of the rotated nanoholes. The multiple diffraction-free beams are exemplified and the performance of holographic metasurfaces are testified by the simulation and experiment results. The utilization of compact metasurface enables the flexible generation of the diffraction-free beams with complex trajectories and tailored wavefronts. It may bring more new applications of diffraction-free beams with on-demand trajectories and customized wavefronts.